2010
DOI: 10.1142/s0217984910024663
|View full text |Cite
|
Sign up to set email alerts
|

The Ground-State Phase Diagrams of Spin-3/2 Ising Model on a Fm/Afm Two-Layer Lattice With Crystal Field

Abstract: The ground-state (GS) phase diagrams of spin-3/2 Ising model for ferromagnetic/antiferromagnetic (FM/AFM) interactions on a two-layer lattice are studied under a constant magnetic field by varying the crystal field values for general coordination number q in detail. Thus, it is found that the system exhibits twenty-nine topologically different GS configurations according to their GS phase diagrams obtained in the (J2/J1, J3/qJ1) planes. As the crystal field becomes more and more negative, the remaining phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Since the GS phase diagrams are obtained at zero absolute temperature, they are very helpful in obtaining the stable solutions in the temperature-dependent models. These GS phase diagrams were presented in our previous paper [33]. So this study of GS's will be our guide for this work concerning the obtaining of the temperature-dependent phase diagrams.…”
Section: The Gs Phase Configurationsmentioning
confidence: 76%
See 1 more Smart Citation
“…Since the GS phase diagrams are obtained at zero absolute temperature, they are very helpful in obtaining the stable solutions in the temperature-dependent models. These GS phase diagrams were presented in our previous paper [33]. So this study of GS's will be our guide for this work concerning the obtaining of the temperature-dependent phase diagrams.…”
Section: The Gs Phase Configurationsmentioning
confidence: 76%
“…with the ground-state phase diagrams obtained and classified as in Ref. [33], the GS phase diagrams are used as a guide in obtaining the temperature-dependent phase diagrams. It is observed that the system presents both second-and first-order phase transitions for all q.…”
Section: The Temperature-dependent Phase Diagramsmentioning
confidence: 99%